Experience in organizing psychological and pedagogical support to families raising children with ASD in the resource center "Nadezhda" of Volzhsky town - Voloshchuk, O.V.; Karpova, S.A.; Kazachkova, E.V. (Autizm i narušenie razvitiâ, 2019)
High-quality psychological and pedagogical support of a child is impossible without work with the family. The process of organizing of psychological and pedagogical support for families raising children with autism spectrum disorders in the resource center of the Regional Rehabilitation Center for Disabled Children "Nadezhda" in Volzhsky, Volgograd Region is described. The process of psychological and pedagogical support of families includes: diagnostics, informational support, teaching parents of competencies in raising and educating of children, involving parents in everyday correctional and development process, leisure activities. The role of interaction between specialists and parents, as well as role of the “School of Effective Parenting”, held in the “Nadezhda” Center emphasized in improving the quality of life of the family. Качественное психолого-педагогическое сопровождение ребенка невозможно без работы с его семьей. Описан процесс организации психолого-педагогического сопровождения семей, воспитывающих детей с расстройствами аутистического спектра, в ресурсном центре Областного реабилитационного центра для детей-инвалидов «Надежда» города Волжский Волгоградской области. Процесс психолого-педагогического сопровождения семей включает: диагностику, информационную поддержку, обучение родителей новым компетенциям в вопросах воспитания и обучения детей, вовлечение родителей в повседневный коррекционно-развивающий процесс, досуговую деятельность. Подчеркнута роль взаимодействия специалистов и родителей, а также «Школы эффективного родительства», действующей в центре «Надежда», в сопровождении семей, обеспечивающем социализацию ребенка и улучшение качества жизни семьи.